Infectious disease health services for refugees and asylum seekers during a time of crisis: a scoping study of six European Union countries - Bozorgmehr, Kayvan; Samuilova, Mariya; Petrova-Benedict, Roumyana; Girardi, Enrico; Piselli, Pierluca; Kentikelenis, Alexander (Health policy, 2018)
Background - Systematic information on infectious disease services provided to refugees and asylum seekers in the European Union (EU) is sparse. We conducted a scoping study of experts in six EU countries in order to map health system responses related to infectious disease prevention and control among refugees and asylum seekers. - Methods - We conducted 27 semi-structured in-depth interviews with first-line staff and health officials to collect information about existing guidelines and practices at each stage of reception in first-entry (Greece/Italy), transit (Croatia/Slovenia), and destination countries (Austria/Sweden). Thematic coding was used to perform a content analysis of interview material. - Results - Guidance on infectious disease screening and health assessments lack standardisation across and—partly—within countries. Data collection on notifiable infectious diseases is mainly reported to be performed by national public health institutions, but is not stratified by migrant status. Health-related information is not transferred in a standardized way between facilities within a single country. International exchange of medical information between countries along the migration route is irregular. Services were reported to be fragmented, and respondents mentioned no specific coordination bodies beyond health authorities at different levels. - Conclusion - Infectious disease health services provided to refugees and asylum seekers lack standardisation in health assessments, data collection, transfer of health-related information and (partly) coordination. This may negatively affect health system performance including public health emergency preparedness.
Gesehen am 18.07.2019